PENGARUH MASSAGE PADA KEHAMILAN TERHADAP PENURUNAN KELUHAN FISIK SELAMA KEHAMILAN - Irma Maya Puspita; Nova Elok Mardliyana; Nur Hidayatul Ainiyah (Jurnal Sains Kebidanan, 2023)
Pregnancy will cause various physical and psychological changes in the first, second, and third trimesters. The changes that occur cause pregnant women discomfort, especially when entering the third trimester. One of the discomforts experienced is that musculoskeletal changes often cause back pain in pregnant women. The research method used is a pre-experimental design with the type of One Group Pretest-Postest. The previous researcher gave a pre-test to the group that would be given the treatment. Then the researcher did the treatment or treatment. After finishing the treatment, the researcher gave a post-test. The number of samples in this study was 70 participants. This research was conducted in Lamongan Regency, East Java. The statistical test results showed a sig value of 0.000, which means that massage during pregnancy reduces physical complaints in the target area of PDNA Lamongan. Massage performed on pregnant women can help reduce physical complaints or discomfort felt by pregnant women, including complaints of back pain, difficulty sleeping (insomnia), and leg cramps.